2016
DOI: 10.3389/fpsyg.2016.01958
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral versus Ocular Visual Impairment: The Impact on Developmental Neuroplasticity

Abstract: Cortical/cerebral visual impairment (CVI) is clinically defined as significant visual dysfunction caused by injury to visual pathways and structures occurring during early perinatal development. Depending on the location and extent of damage, children with CVI often present with a myriad of visual deficits including decreased visual acuity and impaired visual field function. Most striking, however, are impairments in visual processing and attention which have a significant impact on learning, development, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 83 publications
1
44
0
1
Order By: Relevance
“…Furthermore, we observed that children with clinical manifestations of CVDs could present with normal appearing visuo‐associative pathways. This observation is consistent with the recently held view that conventional structural neuroimaging techniques are useful in determining gross changes in cerebral structure but are less effective in terms of identifying more subtle alterations in the integrity of white matter pathways (Martin et al, ). Using conventional MRI, we found also that subjects without CVDs could present with structural white matter lesions at the level of ventral and/or dorsal visual processing streams.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, we observed that children with clinical manifestations of CVDs could present with normal appearing visuo‐associative pathways. This observation is consistent with the recently held view that conventional structural neuroimaging techniques are useful in determining gross changes in cerebral structure but are less effective in terms of identifying more subtle alterations in the integrity of white matter pathways (Martin et al, ). Using conventional MRI, we found also that subjects without CVDs could present with structural white matter lesions at the level of ventral and/or dorsal visual processing streams.…”
Section: Discussionsupporting
confidence: 90%
“…Using conventional MRI, we found also that subjects without CVDs could present with structural white matter lesions at the level of ventral and/or dorsal visual processing streams. A possible explanation is that compensatory neuroplastic reorganization (Guzzetta, Fiori, Scelfo, Conti, & Bancale, ) alters white matter connectivity at the individual level (Martin et al, ) in association with spared visuo‐cognitive functions. Indeed, brain architecture is not static, but represents an ongoing process that continues to modify structural and functional cerebral differentiation (Fazzi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Now, more than ever, there is an increased need for improved accuracy in assessing and diagnosing CVI, owing to its hazardous effect on development and learning . In addition, early diagnosis is warranted, given the fact that neuroplasticity is at its greatest at a young age . However, diagnosis of CVI is challenging in children aged younger than 6 years, particularly in those with a cognitive, language, or motor deficit.…”
Section: Study 1: Development Of Cvit 3–6mentioning
confidence: 99%
“…1,6 In addition, early diagnosis is warranted, given the fact that neuroplasticity is at its greatest at a young age. 7,8 However, diagnosis of CVI is challenging in children aged younger than 6 years, particularly in those with a cognitive, language, or motor deficit. The diverse range of symptoms described above asks for a multidisciplinary diagnostic process that acts at several levels of visual impairment.…”
mentioning
confidence: 99%
“…Oslanjajući se na kliničko iskustvo, Saki i saradnici smatraju da se mora voditi računa o tome da li je pre nastanka CVI možda već postojalo neko oboljenje oka, i obrnuto. Stoga takozvanu radnu definiciju oči su redu, ali ne i mozak treba dopuniti naznakom da se stepen vizuelne disfunkcije kod CVI ne može objasniti oboljenjem vizuelnog sistema pre hijazme (Martín et al, 2016;Sakki et al, 2018). Cerebralno oštećenje vida je krovni termin koji obuhvata vizuelne i vizuelno-perceptivne smetnje koje nisu direktno povezane s oštećenjem perifernog dela vizuelnog sistema, već s disfunkcijama cerebralnih područja uključenih u integraciju i interpretaciju vizuelnih informacija (Goodale, 2013;Lueck, Dutton, & Chokron, 2019).…”
Section: Uvodunclassified